Restructuring post-Communist Russia - Brudny, Yitzhak M.; Frankel, Jonathan; Hoffman, Stefani (Cambridge University Press, 2004)
The end of the Soviet Union was a world-defining moment of the twentieth century, but what comes after Socialism? This collection of original essays - written by Russian scholars and scholars from the West - is a general overview of political change in Russia since 1991, examining the complex interplay between continuity and change that has marked developments in Russia under the leadership first of Boris Yeltsin and now of Vladimir Putin. Rather than see the collapse of state socialism as 'the end of history' or the beginning of the 'transition' to liberal, free market democracy, the contributors instead examine recent Russian history and note that the direction is far from clear. The essays include analysis of Russia specifically, and in comparison with other states of the former Soviet Union and Eastern Europe, and address topics of national identity, demographic change, and the characteristics of Russian democracy.